The Relationship between Family Structure and Maternal Well-being: An Analysis of a Multigenerational Family - Songwathana, Karnjana (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2019)
The increasing divorce rate has resulted in a rise in the number of single mother families. This study aimed to examine the relationship between family structure and level of maternal well-being, especially with regard to the role of multigenerational families on maternal well-being. This study used an in-depth interview with the sample size of 210 mothers in Bangkok province. Using both ordinary least square regression and logistic regression, the results found that women who live in multigenerational families could increase their levels of well-being by reducing their levels of parental aggravation. Hence, policies that support multigenerational families should be promoted in order to reduce mother burdens and improve the family relationship, which is a good start for a sustainable society.